A primer for choosing, designing and evaluating registered reports for qualitative methods - Karhulahti Veli-Matti; Branney Peter; Siutila Miia; Syed Moin (F1000 Research Ltd, 2025)
Registered reports are a publication format that involves peer reviewing studies both before and after carrying out research procedures. Although registered reports were originally developed to combat challenges in quantitative and confirmatory study designs, today registered reports are also available for qualitative and exploratory work. This article provides a brief primer that aims to help researchers in choosing, designing, and evaluating registered reports, which are driven by qualitative methods. Copyright: © 2023 Karhulahti VM et al.
Author keywords
guidelines; open science; qualitative research; registered reports; transparency